2009
DOI: 10.1364/ol.34.001345
|View full text |Cite
|
Sign up to set email alerts
|

Electrically pumped hybrid evanescent Si/InGaAsP lasers

Abstract: Hybrid Si/III-V, Fabry-Perot evanescent lasers are demonstrated, utilizing InGaAsP as the III-V gain material for the first time to our knowledge. The lasing threshold current of 300-m-long devices was as low as 24 mA, with a maximal single facet output power of 4.2 mW at 15°C. Longer devices achieved a maximal single facet output power as high as 12.7 mW, a single facet slope efficiency of 8.4%, and a lasing threshold current density of 1 kA/cm 2 . Continuous wave laser operation was obtained up to 45°C. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 16 publications
(25 reference statements)
3
65
0
1
Order By: Relevance
“…Detailed reviews of these works can be found elsewhere [73,94]. Also, other researchers have shown very similar lasers with InGaAsP, rather than AlGaInAs, multi-quantum well active regions [95].…”
Section: Iii-v Lasers On Siliconmentioning
confidence: 99%
“…Detailed reviews of these works can be found elsewhere [73,94]. Also, other researchers have shown very similar lasers with InGaAsP, rather than AlGaInAs, multi-quantum well active regions [95].…”
Section: Iii-v Lasers On Siliconmentioning
confidence: 99%
“…The pyramids at the top of p-InP layer are results of HCl wet etching during InP substrate removal due to the damaged outer InGaAs layer. With this epilayer transferring technology, the two disparate materials Si and III-V's now can be brought together to realize a variety of active devices on Si, such as lasers (Fang et al, 2006;Fang et al, 2008;Sun et al, 2009), amplifiers (Park et al, 2007a), modulators Kuo et al, 2008), and detectors (Park et al, 2007b). To take the hybrid Si lasers for an example: as seen in Fig.…”
Section: Bonding Proceduresmentioning
confidence: 99%
“…The III-V epilayer has been reported to be AlGaInAs (Fang et al, 2006) or InGaAsP (Sun et al, 2009) quaternary semiconductor compounds, either of which can be epigrown onto an InP substrate with very high crystal quality with current state of the art. In our work (Sun et al, 2009) the thicknesses of the buried SiO 2 layer and the undoped Si device layer are respectively 2.0 μm and 0.9 μm. The Si waveguide is defined using e-beam lithography and SF 6 /C 4 F 8 plasma reactive ion etching as described in detail in previous sections.…”
Section: Bonding Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several types of hybrid III-V/Si lasers, evanescently coupled devices show a great potential for industrial-scale fabrication. Most of the previously demonstrated, evanescently coupled hybrid lasers, including Fabry-Perot [1]- [3], distributed Bragg reflector (DBR) [4], and distributed-feedback (DFB) lasers [5] were based on a molecular (direct) wafer bonding technique which Manuscript received on August 23, 2012. This work was supported by a grant from Intel Corporation and partly supported by the EU-commission through the ERC-grant ULPPIC.…”
Section: Introductionmentioning
confidence: 99%